EFFICACY OF FUNGICIDAL AND BIOCIDAL (PLANT EXTRACTS AND BIO AGENTS) SEED TREATMENT IN MANAGEMENT OF SEED BORNE MYCOFLORA OF FENNEL - BABU LAL FAGODIA; K. S. SHEKHAWAT; S. C. JAIN (The Bioscan, 2014)
Among fungicides used as seed treatment, in vitro Captan proved to be most effective against Aspergillusniger followed by Thiram, Bavistin in improving seed germination and vigourindex by reducing pre and post emergence mortality and number of seedlings showing symptoms. Similarly, among plant extract and bioagents used, garlic extracts followed by neem extracts and Trichoderma harzianum followed by Trichodermavirideproved to be most effective in improving seed germination and vigour index by reducing pre and post emergence mortality and number of seedlings showing symptoms.